‘The system was blinking red’ - Vivian B. Martin (Grounded Theory Review: An International Journal, 2023)
The awareness context has been a source of inspiration for grounded theories for more than 50 years; yet little has been done to extend the theory beyond nursing and the medical field, and a few works on identity. This paper extends the awareness context by examining its role in several high-profile disasters, natural and man-made, where gaining a clear sense of what was going on was often blocked by poor information flow and general communication failures, interpersonal and technological. Selective coding and the introduction of new concepts after analyzing hundreds of pages of documents issued by special commissions in the aftermath of the 9/11 attacks, Hurricane Katrina, the Deepwater Horizon oil spill in the Gulf, and the Sago Mine Disaster not only explain various processes around awareness in the midst of crisis, but also illuminate pre-crisis patterns that, if attended, could have mitigated the impact of the disasters.